Dampak Penyaluran Kredit KUR dan KKI terhadap Pendapatan UMKM Tahu dan Tempe Kecamatan Sebulu Kabupaten Kutai Kartanegara - Ningrum, Dyah Ayu; Manumono, Danang; Trimerani, Resna (Program Studi Agribisnis INSTIPER Yogyakarta, 2024)
Kredit Usaha Rakyat (KUR) is credit or financing provided by banks to UMKM whose businesses are deemed viable but cannot meet the requirements of other financing services offered by banks. This research aims to determine the impact of KUR and KKI credit distribution on the income of tofu and tempeh UMKM, Sebulu District, Kutai Kertanegara Regency. The method used in this research is a quantitative descriptive method. UMKM sampled in this research were 23. The data analysis used is non-linear regression analysis. The research results show that the income of tofu and tempe UMKM in Sebulu District, Kutai Kartanegara Regency is significantly influenced by raw materials and business capital. The impact of KUR and KKI distribution is an increase in the use of raw materials by 80% and an increase in UMKM turnover which also has an impact on increasing the value of savings for UMKM owners who follow KUR by 41% and those who follow KKI by 48%.